Examining Network Structures and Dynamics of World Energy Companies in Stock Markets: A Complex Network Approach - Memon, Bilal Ahmed; Tahir, Rabia (International Journal of Energy Economics and Policy, 2021)
The energy sector occupies a mainstay role in overall growth in the modern worldwide economy. Therefore, it is essential to examine network structures and dynamics of leading energy companies of the world through complex network methods. Because, complex network methods are significant tools of studying the static and dynamics properties of the stock market, which allows us to better comprehend the stock market. We use daily prices of 147 energy stocks belonging to 34 countries of the world from 2006-2019. In addition to the overall sample, we explore networks for two sub-periods to examine the topological evolution during global recession of 2008, and energy and European debt crisis of 2011. Our results show substantial clustering of energy companies based on their geographic position during overall sample period. However, the crisis periods lead to a break in Asian and European clusters and only one prominent cluster appears in all the periods belonging to North American energy companies. We also observe few top US and European based companies occupying important and great global influence positions in the networks. In addition, time-varying topological measures indicate contraction of networks during crisis time, and an expansion in the recovery periods. More implications are also discussed. Keywords: energy companies; complex network; threshold network; minimum spanning tree; stock market; crisis JEL Classifications: C18; E32; E44; G01; G14; G15; G19 DOI: https://doi.org/10.32479/ijeep.11287